Biosynthesis of tetrapyrroles - Jordan, P. M. (Peter M.); ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1991)
The study of the structure and function of tetrapyrrolic compounds has excited the interests of organic chemists, biochemists, botanists and biologists for more than a hundred years. Scientific analysis began with the first descriptions of naturally occurring porphyrins, and progress was made towards understanding the structure of chlorophyll. This was followed by the use of newly available isotopes of carbon and nitrogen to investigate the formation of porphyrins in biological systems. Further discoveries led to the elucidation of the atoms in protoporphyrin IX, made possible by the applicati.
The biosynthesis of 5-aminolaevulinic acid and its transformation into uroporphyrinogen III / Peter M. Jordan -- Mechanism and stereochemistry of the enzymes involved in the conversion of uroporphyrinogen III into haem / Muhammad Akhtar -- The biosynthesis of vitamin B12 / A.I. Scott, P.J. Santander -- Biochemistry of coenzyme F430, a nickel porphinoid involved in methanogenesis / Herbert C. Friedmann, Albrecht Klein, Rudolf K. Thauer -- Biochemistry and regulation of photosynthetic pigment formation in plants and algae / Samuel I. Beale, Jon D. Weinstein -- The structure and biosynthesis of bacteriochlorophylls / Kevin M. Smith -- The genes of tetrapyrrole biosynthesis / Peter M. Jordan, Bob I.A. Mgbeje.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Tetrapyrroles -- Synthesis; Pyrroles -- metabolism; SCIENCE -- Life Sciences -- Biochemistry; Tetrapyrroles -- Synthesis; Tetrapyrrole; Biosynthese; Aufsatzsammlung; Pflanzen; Stoffwechsel; Chemische Synthese; Organisms -- Colouring agents; Electronic books